MANAJEMEN PENGELOLAAN ZIS DALAM UPAYA PENINGKATAN STATUS MUSTAHIK MENJADI MUZAKKI (Studi Analisis Program Bina Insan Mandiri LAZ DASI NTB) - Ningrum, Yuliaprihartin Ningrum; Misri, Zannunil (Mudabbir: Jurnal Manajemen Dakwah, 2022)
Abstract: This study aims to determine the management system of zakat, infaq and shadaqah in LAZ DASI NTB. In addition, this study aims to determine the inhibiting and supporting factors in the management of zakat, infaq and shadaqah in an effort to increase the status of mustahik to muzakki in the Bina Insan Mandiri program of LAZ DASI NTB. This research is motivated by the not yet optimal management and distribution of zakat funds. The type of research used is qualitative research with inductive analysis, data collection techniques by interview and direct observation of the object of research as well as collecting information from various sources such as books, brochures, scientific journals, internet and data from LAZ DASI NTB. The subject of this research is LAZ DASI NTB. Based on the results of the study, LAZ DASI NTB has implemented ZIS management well. In the implementation of ZIS management in an effort to increase the status of mustahik to muzakki in the Bina Insan Mandiri program, LAZ DASI NTB applies management concepts which include planning, organizing, actuating, and controlling the distribution of zakat funds. . In the management of ZIS for the small business development program, the institution has supporting factors, such as: the existence of a zakat pick-up and transfer service system, the existence of entrepreneurship training, marketing and bookkeeping management training, the existence of parties/agencies that work with LAZ DASI NTB, the seriousness of mustahik in carrying out his efforts. In addition to having supporting factors, LAZ DASI NTB also faces several obstacles, such as: lack of manpower in program management, lack of public awareness to provide the rights of the needy and poor through tithing.